Gideon Welles papers - Welles, Gideon, 1802-1878.; Learned, Henry Barrett, 1868-1931.; Welles, Edgar Thaddeus, 1843-1914, secretary of the navy under Lincoln and Johnson; Welles, Gideon, 1802-1878.
Correspondence, diaries, writings, naval records, scrapbooks, and other papers relating to Welles's work as editor of the Hartford Times; his activities as a member of the Democratic Party and, later, the Republican Party in Connecticut state and national politics; his service as U.S. secretary of the navy; and his literary pursuits. Subjects include the role of the U.S. Navy in the Civil War, the presidential administrations of Abraham Lincoln and Andrew Johnson, Welles's commitment to the principles of Thomas Jefferson and Andrew Jackson, the Civil War and Reconstruction, limits and uses of federal and states powers, natural history, naval affairs, relation of newspaper policy and politics, presidential candidates, political parties, and slavery. Includes a fifteen-volume diary kept by Welles as U.S. secretary of the navy; a three-volume restrospective narrative plus notes and journal entries for his early life; drafts of Diary of Gideon Welles, Secretary of the Navy under Lincoln and Johnson (1911), edited by Welles's son, Edgar Thaddeus Welles; and a draft of Welles's book, Lincoln and Seward (1874). Also includes notes of historian Henry Barrett Learned relating to Welles.
Correspondents include Joseph Pratt Allyn, James F. Babcock, Montgomery Blair, Alfred Edmund Burr, Salmon P. Chase, Edward Spicer Cleveland, Schuyler Colfax, Samuel Sullivan Cox, John Adolphus Bernard Dahlgren, Charles A. Dana, Calvin Day, John A. Dix, James Dixon, James Buchanan Eads, Henry H. Elliott, William Faxon, Orris S. Ferry, David Dudley Field, Andrew H. Foote, John Murray Forbes, Gustavus Vasa Fox, R.C. Hale, Joseph R. Hawley, Mark Howard, Amasa Jackson, Thornton A. Jenkins, Richard M. Johnson, James E. Jouett, Andrew T. Judson, Henry Mitchell, Edwin D. Morgan, John M. Niles, Nathaniel Niles, Foxhall A. Parker, William Patton, Hiram Paulding, J.J.R. Pease, William V. Pettit, James J. Pratt, Albert Smith, Joseph Smith, Sylvester S. Southworth, Daniel D. Tompkins, Charles Dudley Warner, Thurlow Weed, Edgar Thaddeus Welles, Mary Hale Welles, and Charles Wilkes.
Microfilm edition of series 1-8 available
Microfilm produced from originals in the Manuscript Division.
U.S. secretary of the navy and newspaper editor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Allyn, Joseph Pratt, -- 1833-1869 -- Correspondence; Babcock, James F. -- 1809-1874 -- Correspondence; Blair, Montgomery, -- 1813-1883 -- Correspondence; Burr, Alfred Edmund, -- 1815-1900 -- Correspondence; Chase, Salmon P. -- 1808-1873 -- Correspondence; Cleveland, Edward Spicer -- Correspondence; Colfax, Schuyler, -- 1823-1885 -- Correspondence; Cox, Samuel Sullivan, -- 1824-1889 -- Correspondence; Dahlgren, John Adolphus Bernard, -- 1809-1870 -- Correspondence; Dana, Charles A. -- 1819-1897 -- Correspondence; Day, Calvin -- Correspondence; Dix, John A. -- 1798-1879 -- Correspondence; Dixon, James, -- 1814-1873 -- Correspondence; Eads, James Buchanan, -- 1820-1887 -- Correspondence; Elliott, Henry H. -- Correspondence; Faxon, William, -- 1822-1883 -- Correspondence; Ferry, Orris S. -- 1823-1875 -- Correspondence; Field, David Dudley, -- 1805-1894 -- Correspondence; Foote, Andrew H. -- 1806-1863 -- Correspondence; Forbes, John Murray, -- 1813-1898 -- Correspondence; Fox, Gustavus Vasa, -- 1821-1883 -- Correspondence; Hale, R. C. -- 1812-1863 -- Correspondence; Hawley, Joseph R. -- 1826-1905 -- Correspondence; Howard, Mark, -- 1817-1887 -- Correspondence; Jackson, Amasa -- Correspondence; Jackson, Andrew, -- 1767-1845.; Jefferson, Thomas, -- 1743-1826.; Jenkins, Thornton A. -- 1811-1893 -- Correspondence; Johnson, Andrew, -- 1808-1875.; Johnson, Richard M. -- 1781-1850 -- Correspondence; Jouett, James E. -- 1828-1902 -- Correspondence; Judson, Andrew T. -- 1784-1853 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Mitchell, Henry, -- 1830-1902 -- Correspondence; Morgan, Edwin D. -- 1811-1883 -- Correspondence; Niles, John M. -- 1787-1856 -- Correspondence; Niles, Nathaniel, -- 1791-1869 -- Correspondence; Parker, Foxhall A. -- 1821-1879 -- Correspondence; Patton, William, -- 1798-1879 -- Correspondence; Paulding, Hiram, -- 1797-1878 -- Correspondence; Pease, J. J. R. -- Correspondence; Pettit, William V. -- Correspondence; Pratt, James J. -- Correspondence; Smith, Albert, -- 1805-1870 -- Correspondence; Smith, Joseph, -- 1790-1877 -- Correspondence; Southworth, Sylvester S. -- Correspondence; Tompkins, Daniel D., -- 1774-1825 -- Correspondence; Warner, Charles Dudley, -- 1829-1900 -- Correspondence; Weed, Thurlow, -- 1797-1882 -- Correspondence; Welles, Edgar Thaddeus, -- 1843-1914 -- Correspondence; Welles, Mary Hale, -- 1817-1895 -- Correspondence; Wilkes, Charles, -- 1798-1877 -- Correspondence; United States. -- Navy; United States. -- Navy -- History -- Civil War, 1861-1865.; United States. -- Navy Department; Democratic Party (U.S.); Republican Party (U.S. : 1854- ); Hartford times; American newspapers -- Connecticut; Federal government -- United States